(untitled) (Research, Society and Development, 2023)
Spirituality is a constitutive part of palliative care for patients in a weakened state of health. The objective of this work was to analyze, through a narrative review of the literature, the definitions and importance of spirituality from the perspective of the patient, the family and the professionals of the multidisciplinary team involved, in addition to identifying techniques and approaches to work with it. A search was carried out in the databases: Virtual Health Library, National Library of Medicine, Scientific Electronic Library Online and EbscoHost, in English and Portuguese, from May to June 2022, with 48 studies found , 20 met the inclusion criteria. After reading the texts, beliefs and spiritual practices could be associated with the relief of anxiety, improvement of physiological and psychological conditions, adherence to treatment, acceptance, social support, motivation, in addition to the meaning of life and death. However, despite the benefits of this form of care, studies in the hospital context are still recent and punctual. While most patients and caregivers attach great value to spirituality, health professionals still have little training and willingness to provide this assistance. Therefore, for a more humanized and effective palliative treatment, it is important that there is greater probing, communication and preparation of professionals to work with spirituality, promoting the reduction of suffering and expanding the quality of life of patients and their families.